Legal Certainty of Grondkaart as Proof of Control of PT. Kereta Api Indonesia (PERSERO) in the Implementation of Land Registration - Anugrah Ganda Mahardika; Aan Efendi; Ainul Azizah (Universitas KH. Abdul Chalim Mojokerto, 2026)
Grondkaart is administrative evidence that records the ownership of railway land in the past. However, the unclear legal status of Grondkaart has given rise to various conflicts that often end up in court. There is legal uncertainty regarding land rights in the form of overlapping other rights issued above Grondkaart or land rights that are only based on Grondkaart itself. Critical evaluation of existing regulations and identification of problems from previous case studies will provide a strong foundation for formulating recommendations for improvement and refinement of the concept in order to ensure legal certainty. The research method used is normative legal research, namely, research on legislation, court decisions, and legal doctrines to understand positive law and resolve legal issues. The results of this study indicate that the Grondkaart has a strategic function as initial evidence of land ownership by PT. KAI (Persero), but its legal certainty will only be realized if the registration or conversion process of rights has been carried out in accordance with the provisions of laws and regulations. The Grondkaart cannot be used as the only legitimate basis for proving ownership in the land registration system in Indonesia. In order to maximize the transitional function of the Grondkaart as a basis for temporary recognition, the government needs to issue a policy that clearly explains its legal status within the framework of rights conversion. This can be done through the technical guidelines of the Ministry of ATR/BPN, which regulate the procedure for integrating historical documents into the national land registration system. Efforts are also needed to increase factual verification of physical control in the field, including the involvement of the community and interested parties. Thus, proof based on the Grondkaart becomes more objective, transparent, and in accordance with the precautionary principle in the national land registration system.